Modifications to the Special Data Dissemination Standard Plus. (Policy Papers; Policy Paper ;, 2014)
The Special Data Dissemination Standard Plus (SDDS Plus) was established in October 2012 to reinforce and supplement the Fund's Data Standards Initiatives and assist Fund members who decide to adhere to the SDDS Plus with regard to the publication of comprehensive, timely, accessible, and reliable economic and financial statistical data in a world of continuing economic and financial integration. The SDDS Plus also requires adherents to disseminate metadata to promote public knowledge and understanding of their compilation practices with respect to the required data categories. Following consultations conducted between Fund staff and members' authorities of potential adherents to the SDDS Plus, it appeared necessary to introduce certain modifications to the SDDS Plus legal framework to facilitate adherence. These modifications are consistent with views expressed by Executive Directors in informal discussions with staff, and entail (i) extending the timeliness of three data categories and (ii) maintaining consistency with the principle underlying the SDDS Plus framework under which subscribers may chose to adopt new methodologies or continue to follow older ones. The Executive Board approved, on a lapse-of-time basis, the proposed decision in the paper. The existing rules governing the SDDS Plus are superseded by the new SDDS Plus legal text.